Rapid assessment of tiered referral system at a hospital of West Sumatra, Indonesia - Dian Furwasyih; Orsolya Varga (Universitas Airlangga, 2020)
Objective: The purpose of this study was to assess patients’ perception on tiered maternal referral system (during pregnancy, delivery, and postpartum) in a hospital of West Sumatra of Indonesia.Materials and Methods: The design was a cross-sectional interview survey. A convenient sampling technique was used to recruit 134 sample. Our study was approved by the Committee of the Research Ethics of the Faculty of Medicine, Andalas University number 002/KEP/FK/2018. An interview guideline was prepared and translated into Bahasa Indonesia. There were two interviewers recruited and trained to collect information for the study. Each interview took approximately 12 minutes and were recorded using mobile phone. Data from the interviews were analysed by using QSR NVIVO 10 and MS Excel 2010.Results: The vast majority of the respondents reported that there was sufficient understanding of the services and the structure of the overall tiered referral system. The complaints addressed the issue of administrative procedure, accessibility, and equity, waiting time and card activation, ease of obtaining referral letter in the primary level of healthcare, and transport duration when the patient has to be referred to advance level of healthcare.Conclusion: The functional use of electronic referral system is an urge for solution. Future studies on patients’ perception and assessment toward healthcare providers’ opinion should be carried out to increase the service quality.